Specific functional roles in mammals - McManus, Michael (Henry Stewart Talks, 2007)
Introduction to noncoding RNAs, Functional biology of RNA interference pathways, Structural overview of microRNAs, Modes of action of small noncoding RNAs, An example of a microRNA target, Where are small RNAs expressed?, Harnessing the RNA interference pathway for genetic analysis, Genetic ablation of the catalytic engine for small RNA production in the mouse
Reviewed at 2016/10/13